Vietnam perspective - Johnson, Dennis; Rosofsky, Steve (Chicago : Encyclopaedia Britannica Educational Corporation, 1985)
Gives a chronology of foreign involvement in Southeast Asia, highlighting America's participation in the Vietnam War. Presents key factors in the conflict, from the Truman and Eisenhower administration's commitment to the French in Indochina, through the Kennedy and Johnson years, to the Nixon administration's reorientation of U.S.-Asian policy.
Keywords: Vietnamese Conflict, 1961 -- 1975 -- United States; Indochina -- Foreign relations -- United States; United States -- Foreign relations -- Indochina; Indochina -- History -- 1945.